2015
DOI: 10.1177/0301006615594261
|View full text |Cite
|
Sign up to set email alerts
|

Depth-of-Focus Affects 3D Perception in Stereoscopic Displays

Abstract: Stereoscopic systems present binocular images on planar surface at a fixed distance. They induce cues to flatness, indicating that images are presented on a unique surface and specifying the relative depth of that surface. The center of interest of this study is on a second problem, arising when a 3D object distance differs from the display distance. As binocular disparity must be scaled using an estimate of viewing distance, object depth can thus be affected through disparity scaling. Two previous experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Thus, to judge the depth of our stimulus, observers should have scaled the binocular disparity in the stimulus using an estimate of its egocentric distance (Bradshaw et al, 1996). This indirect effect on depth perception has already been observed in studies on the effect of focus cues on depth perception (Watt et al, 2005; Hoffman et al, 2008; Vienne et al, 2015). Our results thus suggest that bias in perceived depth indirectly ensues from undershoots in the disparity-driven accommodation response.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Thus, to judge the depth of our stimulus, observers should have scaled the binocular disparity in the stimulus using an estimate of its egocentric distance (Bradshaw et al, 1996). This indirect effect on depth perception has already been observed in studies on the effect of focus cues on depth perception (Watt et al, 2005; Hoffman et al, 2008; Vienne et al, 2015). Our results thus suggest that bias in perceived depth indirectly ensues from undershoots in the disparity-driven accommodation response.…”
Section: Discussionsupporting
confidence: 57%
“…More recent studies have suggested that both accommodation and blur may provide a more useful cue to depth than expected (Watt et al, 2005; Held et al, 2012). Some experimental studies reported reduced depth constancy when the stimulus was displayed with conflicting accommodation and vergence distances, such that depth perception was biased toward the screen plane distance (Watt et al, 2005; Hoffman et al, 2008; Vienne et al, 2015). The reported bias could not be attributed to the accommodative response (i.e., extra-retinal signal) or the accommodative stimulus (i.e., retinal blur) because accommodation responses were not measured.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is conceivable that the mean perceived distance was not affected because subjects did not rely on the same cues to estimate distance. For example, some participants might assign less weight to the vergence cue in favor of others (e.g., the accommodation or focus cue which signals screen distance, Vienne, Blonde´, & Mamassian, 2015), and thus, they perceive less depth between the object and the screen.…”
Section: Discussionmentioning
confidence: 99%
“…To help in the task, we displayed a transparent cylinder, so that observers could use the front and back face of the cylinder to better estimate its depth (Vienne et al., 2015). In this experiment, we used the method of constant stimuli to vary the depth ratio of the cylinder (i.e., the cylindricality).…”
Section: Experiments 4: the Effect Of Convergent Cameras On Depth Percmentioning
confidence: 99%
See 1 more Smart Citation